(3QSGdI HOA GdNdbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Cdg GdMb heHOY Ydg GdNdb Ef CMSf eG CHJOF Hg MeO GdHGQ GdefRg Yf GdCRd hGdCRdjI s
(3BNQgG (B:s
(3hehai cd CeI CLdgG HYO EbGeI GdMLL JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdMb YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B85s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds